A pilot study on the use of biolase in the treatment of recurrent aphthous ulcer - Mustafa, Nazih Shaban; Kashmola, Muhanad Ali Hamdon; Baharudin, Muhamad Zulhelmi; Hashim, Hafiz Izzuddin; Abdul Jabbar, Omar; Mustafa Al-Ahmad, Basma Ezzat (Piracicaba Dental School – UNICAMP, 2018)
Recurrent Aphthous Ulcer (RAU) is a common oral pathology that produces pain which affects the lifestyle of the patient. Its aetiology and pathogenesis still remain unclear. A considerable number of treatments are available with the main goal directed towards pain relief. Previous studies on RAU treatment using low level laser therapy (LLLT) show immediate pain relief after application. Aim: This study aims to evaluate and compare treatment effectiveness in relieving pain provided by Waterlase (BIOLASE) LLLT and conventional topical corticosteroid using Triamcinolone Acetonide 0.1% dental paste. Methods: Thirty (30) volunteered patients of age between 18-27 years old were divided into two groups. Each group consists of 15 patients with 7 males and 8 females. Group 1 patients were treated by using LLLT while group 2 patients were treated by using triamcinolone acetonide 0.1%. The patient’s details, pain intensity and clinical photographs were recorded in a specially prepared case sheet. Mann-Whitney U test was used to compare significance in pain reduction provided by both methods of treatment. Results: Both groups showed significant pain reduction immediately, day 3 and day 7. Higher reduction in pain intensity was observed immediately (p=0.001) and 3 days (p=0.002) after treatment in group 1 patients (LLLT) compared to group 2 patients (triamcinolone acetonide 0.1%). Conclusion: Waterlase (BIOLASE) LLLT is clinically more effective in relieving pain compared to Triamcinolone Acetonide 0.1%.